PENGARUH PENGETAHUAN, KEMAMPUAN, DAN KETERAMPILAN TERHADAP KINERJA BISNIS WIRAUSAHA MUDA DI KECAMATAN TAMPAN KOTA PEKANBARU - Sukriani, Nurul; Febrina, Dian; Dewi, Diana Sri (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to analyze the influence of knowledge, ability, and skills on the business performance of young entrepreneurs in Tampan District, Pekanbaru City. The data analysis method used is quantitative. Data sources consist of primary and secondary data obtained through questionnaires and interviews. The population of this study comprises young entrepreneurs in Tampan District, Pekanbaru City. As the exact population size is unknown, the sample was determined using the Wibisono method, resulting in a sample of 97 respondents. The results indicate that there is a simultaneous significant effect of knowledge, ability, and skills on the business performance of young entrepreneurs in Tampan District, Pekanbaru City. Partially, knowledge, ability, and skills also show a significant effect on the business performance of young entrepreneurs in Tampan District, Pekanbaru City